2007
DOI: 10.1111/j.1533-2500.2007.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Efficacy Beliefs Predict Sustained Long‐Term Sick Absenteeism in Individuals With Chronic Musculoskeletal Pain

Abstract: Recovery beliefs are assumed to predict rehabilitation outcomes and return-to-work in various clinical conditions but are less frequently assessed in musculoskeletal disorders. We tested the hypothesis that recovery beliefs constitute a risk factor for sustained long-term sick absenteeism in men and women suffering from nonspecific chronic musculoskeletal disorders. A total of 233 subjects with a recent or ongoing experience of long-term sick leave were included in a prospective design. Subjects answered a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 37 publications
(34 reference statements)
4
30
0
Order By: Relevance
“…In total, 32 quantitative studies investigated the association between expectations regarding recovery or RTW and work participation (Table 1: Audhoe et al 2012; Besen et al 2015; Boot et al 2008; Busch et al 2007; Carriere et al 2015a, b; Carstens et al 2014; Coggon et al 2013; Cowan et al 2012; Du Bois et al 2009; Ekberg et al 2015; Gross and Battié 2010; Hou et al 2008, 2012; Iakova et al 2012; Jensen et al 2013; Johansson et al 2010; Lindell et al 2010; Magnussen et al 2007b; Murgatroyd et al 2016; Nieuwenhuijsen et al 2013; Opsahl et al 2016; Reme et al 2009; Richter et al 2011; Rönnberg et al 2007; Sampere et al 2012; Sluiter and Frings-Dresen 2008; Spector et al 2012; Truchon et al 2012; Turner et al 2008; Vuistiner et al 2015; Wåhlin et al 2012). The majority of these studies found evidence of a positive association, which suggests that having positive expectations about one’s recovery or chances of RTW has a positive effect on work participation for employees with health problems (Audhoe et al 2012; Besen et al 2015; Busch et al 2007; Carriere et al 2015a, b; Carstens et al 2014; Cowan et al 2012; Du Bois et al 2009; Ekberg et al 2015; Gross and Battié 2010; Hou et al 2008, 2012; Jensen et al 2013; Johansson et al 2010; Lindell et al 2010; Magnussen et al 2007b; Murgatroyd et al 2016; Opsahl et al 2016; Reme et al 2009; Richter et al 2011; Rönnberg et al 2007; Sampere et al 2012; Sluiter and Frings-Dresen 2008; Spector et al 2012; Truchon et al 2012; Vuistiner et al 2015; Wåhlin et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 32 quantitative studies investigated the association between expectations regarding recovery or RTW and work participation (Table 1: Audhoe et al 2012; Besen et al 2015; Boot et al 2008; Busch et al 2007; Carriere et al 2015a, b; Carstens et al 2014; Coggon et al 2013; Cowan et al 2012; Du Bois et al 2009; Ekberg et al 2015; Gross and Battié 2010; Hou et al 2008, 2012; Iakova et al 2012; Jensen et al 2013; Johansson et al 2010; Lindell et al 2010; Magnussen et al 2007b; Murgatroyd et al 2016; Nieuwenhuijsen et al 2013; Opsahl et al 2016; Reme et al 2009; Richter et al 2011; Rönnberg et al 2007; Sampere et al 2012; Sluiter and Frings-Dresen 2008; Spector et al 2012; Truchon et al 2012; Turner et al 2008; Vuistiner et al 2015; Wåhlin et al 2012). The majority of these studies found evidence of a positive association, which suggests that having positive expectations about one’s recovery or chances of RTW has a positive effect on work participation for employees with health problems (Audhoe et al 2012; Besen et al 2015; Busch et al 2007; Carriere et al 2015a, b; Carstens et al 2014; Cowan et al 2012; Du Bois et al 2009; Ekberg et al 2015; Gross and Battié 2010; Hou et al 2008, 2012; Jensen et al 2013; Johansson et al 2010; Lindell et al 2010; Magnussen et al 2007b; Murgatroyd et al 2016; Opsahl et al 2016; Reme et al 2009; Richter et al 2011; Rönnberg et al 2007; Sampere et al 2012; Sluiter and Frings-Dresen 2008; Spector et al 2012; Truchon et al 2012; Vuistiner et al 2015; Wåhlin et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of these studies found evidence of a positive association, which suggests that having positive expectations about one’s recovery or chances of RTW has a positive effect on work participation for employees with health problems (Audhoe et al 2012; Besen et al 2015; Busch et al 2007; Carriere et al 2015a, b; Carstens et al 2014; Cowan et al 2012; Du Bois et al 2009; Ekberg et al 2015; Gross and Battié 2010; Hou et al 2008, 2012; Jensen et al 2013; Johansson et al 2010; Lindell et al 2010; Magnussen et al 2007b; Murgatroyd et al 2016; Opsahl et al 2016; Reme et al 2009; Richter et al 2011; Rönnberg et al 2007; Sampere et al 2012; Sluiter and Frings-Dresen 2008; Spector et al 2012; Truchon et al 2012; Vuistiner et al 2015; Wåhlin et al 2012). However, some of these studies indicated that the effect was dependent on the subgroup of participants or the form of expectations (Ekberg et al 2015; Gross and Battié 2010; Murgatroyd et al 2016; Sluiter and Frings-Dresen 2008; Wåhlin et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, self-efficacy plays an important role in coping with chronic physical illnesses and engaging in health-promoting behavior [28][29][30][31][32][33][34][35][36]; we would expect it to play no less of a role in serious mental illness. Second, these data suggest that any effort to improve the wellness of these adults with serious mental illnesses will need to address self-efficacy as a foundation for improving self-care for their physical health needs.…”
Section: Discussionmentioning
confidence: 99%